MEDIATION EFFECTS OF WORK STRESS IN THE EFFECT OF CONFLICT ON AUDITOR PERFORMANCE - Rahardjo, Kusuma Adi; Masyuri, Mohammad Ali (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
One of the most reliable information in the world of economics is financial statements. This requires the Public Accounting Firm to have adequate and quality Human Resources in order to provide maximum results. The resources they have are auditors. This study aims to examine the effect of conflict on work stress and its impact on the performance of auditors working at KANTOR AKUNTAN PUBLIK in East Java. This study used 190 samples of respondents. The sampling method used in this study is a purposive random sampling method and the type of data used in this study is primary data. The data analysis method used is Structural Equation Modeling (SEM) with a PLS approach. The results showed that conflict and work stress had a significant effect on performance. The results also show that work stress is able to mediate the influence of conflict on auditor performance